Cost and Financing Higher Education by Nepalese Student in Australia, Student Loans and Role of Bank in Nepal - Upadhyay-Dhungel, Kshitiz; Lamichhane, Shreeram (Banking Journal, 2011)
In the last few decades, lots of youth have migrated to foreign lands from Nepal for their study. An estimated 20,000 students leave the country annually to pursue their further education abroad and a huge sum of more than NRs 2000 million outflows for this purpose. United Kingdom (UK), United States of America (USA), Australia are the preferred destinations of Nepalese students. In recent days, Australia has been found as the top destination for them. Currently, Nepal stands in the 6th position in terms of number of foreign students studying in Australia. So, in this study we attempted to find the cost of living and studying in Australia by Nepalese students, source of funding and the role of Nepali banks in providing support to these students. As research participants, students residing in Australia for their higher study were selected through random sampling. A set of questionnaire was prepared by reviewing relevant literature survey. Fifty participants (randomly selected) were contacted through e-mail. Only 16 of them filled up the questionnaire completely and returned (response rate, 32%). Later on after tabulation of data, two information rich respondents were purposefully selected for detail study. They were regularly contacted through email and through Skype internet chatting was done. Cost of migration, living and study is very high in Australia. Students were found meeting their cost requirements through various sources. Among them family was the initial source of funding and at the later stage seemed to be mitigated their educational and survival expenses through part time job, scholarships and stipends. None of them were found to have education loan as a source of educational funding. Hence the role of bank is not apparent. Provisions of collateral, complex documentation procedures and high interest rate for student loan are the reasons why students are not interested in education loans. Education loan market can be the area where banks can think of investment. Furthermore subsidised rate of interest and easy documentation and repayment system can lure the students to take loans. This can also be worked out with collaboration with government or Educational institution as practised in other parts of world. Further in depth study of similar kinds is recommended. Key words: Education loan; student loan; financing higher education; repayment; role of bank DOI: http://dx.doi.org/10.3126/bj.v1i1.5143 Banking Journal Vol.1(1) 2011: 46-62